2017
DOI: 10.4269/ajtmh.16-0389
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Orbital Inflammation Caused by Leishmania braziliensis

Abstract: Abstract. Orbital biopsy of nonspecific orbital inflammation, commonly referred to as "orbital pseudotumor," typically shows a combination of polyclonal lymphocytes, plasmocytes, leukocytes, macrophages, and variable degrees of collagen deposition. Herein, we report a patient with a positive history of mucocutaneous leishmaniasis who presented with an orbital mass with a histological profile of idiopathic orbital inflammation. Immunohistochemical and molecular analysis of the orbital specimens demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Lowen et al's [ 27 ] study enrolled 55 cases for exploring the histopathologic and immunohistochemical pattern of NSOI; they found that NSOI displayed a predominance of T cells, which coordinates with our results. Despite the immune alteration, variable degrees of collagen deposition also are considered an essential pathologic change of NSOI as previously reported [ 28 , 29 ]. However, the cellular mechanism remains not fully understood.…”
Section: Discussionmentioning
confidence: 82%
“…Lowen et al's [ 27 ] study enrolled 55 cases for exploring the histopathologic and immunohistochemical pattern of NSOI; they found that NSOI displayed a predominance of T cells, which coordinates with our results. Despite the immune alteration, variable degrees of collagen deposition also are considered an essential pathologic change of NSOI as previously reported [ 28 , 29 ]. However, the cellular mechanism remains not fully understood.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to the classical immune theory, some scholars believed that OIP might be secondary to or associated with viral, bacterial or other pathogen infections, such as Epstein–Barr virus (EBV), Streptococcus, HIV, herpes zoster, and Leishmania braziliensis, among which EBV is mainly reported [ 46 50 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Lesions are destructive and principally affect the skin and mucus membranes in the oral, nasal, and oropharyngeal tracts (Ministeŕio da Saúde, 2017;Conceicão-Silva and Morgado, 2019). Furthermore, studies have reported the occurrence of lesions in the eye (Cruz et al, 2017) and larynx (Silva et al, 2017). The DNA of the parasite has also been detected in bone marrow of immunocompromised patients (Gontijo et al, 2002;Silva et al, 2002).…”
mentioning
confidence: 99%